Silk scaffolding drives self-assembly of functional and mature human brain organoids - Sozzi, Edoardo; Kajtez, Janko; Bruzelius, Andreas; Wesseler, Milan Finn; Nilsson, Fredrik; Birtele, Marcella; Larsen, Niels B.; Ottosson, Daniella Rylander; Storm, Petter; Parmar, Malin; Fiorenzano, Alessandro (Frontiers in Cell and Developmental Biology, 2022)
Human pluripotent stem cells (hPSCs) are intrinsically able to self-organize into cerebral organoids that mimic features of developing human brain tissue. These three-dimensional structures provide a unique opportunity to generate cytoarchitecture and cell-cell interactions reminiscent of human brain complexity in a dish. However, current in vitro brain organoid methodologies often result in intra-organoid variability, limiting their use in recapitulating later developmental stages as well as in disease modeling and drug discovery. In addition, cell stress and hypoxia resulting from long-term culture lead to incomplete maturation and cell death within the inner core. Here, we used a recombinant silk microfiber network as a scaffold to drive hPSCs to self-arrange into engineered cerebral organoids. Silk scaffolding promoted neuroectoderm formation and reduced heterogeneity of cellular organization within individual organoids. Bulk and single cell transcriptomics confirmed that silk cerebral organoids display more homogeneous and functionally mature neuronal properties than organoids grown in the absence of silk scaffold. Furthermore, oxygen sensing analysis showed that silk scaffolds create more favorable growth and differentiation conditions by facilitating the delivery of oxygen and nutrients. The silk scaffolding strategy appears to reduce intra-organoid variability and enhances self-organization into functionally mature human brain organoids.